Fish Oil Containing Pro-Resolving Mediators Enhances the Antioxidant System and Ameliorates LPS-Induced Inflammation in Human Bronchial Epithelial Cells - Alfio Distefano; Laura Orlando; Sebastiano Giallongo; Emanuela Tropea; Mariarita Spampinato; Annalisa Santisi; Lucia Longhitano; Giuseppe Parisi; Salvatore Leonardi; Arcangelo Russo; Massimo Caruso; Michelino Di Rosa; et al. (MDPI AG, 2024)
Fish oil, renowned for its high content of omega-3 fatty acids, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), has gained considerable attention for its potential health benefits. EPA and DHA exhibit anti-inflammatory effects by promoting the production of specialized pro-resolving mediators (SPMs), such as resolvins and protectins. Fish oil has been studied for its potential to reduce bronchial inflammation, a key feature of respiratory conditions like asthma and COPD. This study investigates the cellular mechanisms of fish oil in an in vitro model of lung inflammation using lipopolysaccharide (LPS) on a healthy human bronchial epithelium cell line. LPS exposure for 24 h reduced cell viability, elevated reactive oxygen species (ROS), depleted glutathione (GSH), and induced mitochondrial depolarization, indicating oxidative stress and inflammation. Fish oil administration significantly mitigated ROS production, prevented GSH depletion, and reduced mitochondrial depolarization. This was associated with the upregulation of the endogenous antioxidant system, evidenced by restored GSH levels and the increased gene expression of glutathione peroxidase (GPX), catalase (CAT), superoxide dismutase 1 (SOD1), and superoxide dismutase 2 (SOD2). Fish oil also suppressed IL-6 and IL-1β expression and increased anti-inflammatory cytokine IL-10 expression. Furthermore, fish oil upregulated the expression of pro-resolving mediator receptors, suggesting a role in inflammation resolution. These findings highlight the potential of fish oil supplementation as a preventive measure against pulmonary diseases characterized by unresolved inflammation such as lung inflammation.